2014
DOI: 10.1177/1066896914542125
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Cribriform Carcinoma, a Morphologic Pattern Associated With Low Survival

Abstract: Colorectal carcinoma is one of the most common cancers in the human body. Colorectal carcinoma is a heterogeneous disease with variegated morphological patterns; some have shown themselves to have prognostic value. The World Health Organization classification recognizes many histological variants associated with adverse prognostic factors, one is the cribriform colonic carcinoma (CCC). In this work, we analyzed 18 cases of CCC compared with 228 conventional adenocarcinomas of colon, with the hypotheses that CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
2
11
0
1
Order By: Relevance
“…We observed an association of high areal density of cribriform structures with poor prognosis. This finding is in agreement with reports of poor prognosis in cribriform‐comedo type adenocarcinoma, a rare CRC subtype (25‐27). However, the prognostic significance of the overall extent of cribriform pattern, as shown in our study, has been unknown in CRC.…”
Section: Discussionsupporting
confidence: 93%
“…We observed an association of high areal density of cribriform structures with poor prognosis. This finding is in agreement with reports of poor prognosis in cribriform‐comedo type adenocarcinoma, a rare CRC subtype (25‐27). However, the prognostic significance of the overall extent of cribriform pattern, as shown in our study, has been unknown in CRC.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to other studies, we found cribriform pattern of the invasive component to be an adverse factor of MCP6 23 and in all colorectal adenocarcinoma 24. Introduced in the latest WHO classification as a morphological subtype of colorectal adenocarcinoma, cribriform carcinoma of the colon resembles cribriform carcinomas of the breast or salivary glands and is often associated with comedo-type necrosis.…”
Section: Discussionsupporting
confidence: 88%
“…2 Recently, a study by Lino-Silva et al has highlighted a negative outcome for this entity. 11 Moreover, the majority of the cases enrolled in that study showed adverse prognostic findings such as high stage, lymphovascular invasion, lymph nodes metastasis in >5 of the harvested ones, and lower 5-year survival than conventional adenocarcinomas histotype. 11 Moreover, Kim et al .…”
Section: Colonic Cribriform Comedo-type Adenocarcinomamentioning
confidence: 79%
“…11 Moreover, the majority of the cases enrolled in that study showed adverse prognostic findings such as high stage, lymphovascular invasion, lymph nodes metastasis in >5 of the harvested ones, and lower 5-year survival than conventional adenocarcinomas histotype. 11 Moreover, Kim et al . demonstrated a negative prognostic impact for those colorectal carcinomas with a cribriform component characterized by microsatellite instability high (MSI-H), in terms of shorter disease-free survival.…”
Section: Colonic Cribriform Comedo-type Adenocarcinomamentioning
confidence: 79%